English Teachers’ Readiness for Home-Based Learning: Its Relationship to Teachers’ Performance - Arciaga, Mary Cecille (Journal of Interdisciplinary Perspectives, 2024)
. The researcher aimed to determine the relationship between English teachers' readiness for home-based learning and their performance. The study's presumed hypothesis was tested using a descriptive correlational design with a significance level of 0.05. The data were analyzed using a variety of statistical measures, including frequency count, mean, and multiple regression analysis, to answer the study question. Furthermore, the researcher used a reliable and valid instrument designed by Mansor et al. (2021) to measure the level of readiness for home-based learning among teacher respondents. Meanwhile, a documentary analysis was used to evaluate the English teachers' performance. The study was evaluated and approved for implementation by the LCUP-REC. To assure consistency, the researcher asked 252 teachers from nine (9) schools in one of Bulacan's educational districts to complete the standardized surveys using Google Form while maintaining rigid anonymity. The data were examined and handled statistically using Statistical Packages for Social Sciences (SPSS). The results indicated a value larger than the predetermined 0.05 threshold of significance. The researcher failed to reject the null hypothesis, which states that there is not a significant relationship between English teachers' readiness for home-based learning and their performance. Furthermore, the study proposed a faculty development program concentrating on English language competency as part of teachers' ongoing professional development to improve their level of readiness for home-based learning, particularly in terms of subjective norms.